Application of the Object Oriented Analysis Method and Design Web Profile at MA Darussalam Pangkal Pinang - Umar Faruq Vista; Nurhaeka Tou; Putri Mentari Endraswari (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2023)
Web profile is one of the effective media for disseminating information in introducing the institution to the wider community. This is what is used by many government and private agencies, one of which is an educational institution or school. MA (Madrasah Aliyah) Darussalam Pangkalpinang is one of the education institutions under the auspices of the Ministry of Religion of the Republic of Indonesia. MA Darussalam Pangkalpinang does not currently have a Web Profile as a means of disseminating information to the public at large. This research has the objective of helping MA Darussalam Pangkalpinang to have a medium for disseminating information that can be accessed by the wider community easily, effectively, and efficiently. In making the Web Profile in this study, the Object Oriented Analysis and Design (OOAD) method was used which has several work stages that can optimize web performance to be optimal. Based on the OOAD method in this study, there are 5 diagrams used, including Use Case, Activity, Collaboration, Sequence, and Class Diagrams. The result of applying the OOAD method is a website-based school profile application that contains useful information belonging to the school, especially MA Darussalam Pangkalpinang which can be accessed by students and the wider community. With this web profile, it is hoped that it will help MA Darussalam in promoting their school more broadly and building a better school branding.